Sequential Metastatic Breast Cancer Chemotherapy: Should the Median be the Message? - Jung, Su Yon; Rosenzweig, Margaret (Frontiers in Public Health, 2013)
Background: Counseling and anticipatory guidance of the expected course of treatment for women newly diagnosed with metastatic breast cancer (MBC) are difficult due to multiple factors influencing survival following metastatic breast cancer therapy. In order to better tailor counseling at the onset and through the duration of metastatic breast cancer we used non-clinical trial data to better characterize real life experience of sequential metastatic breast cancer treatment. We examined the following aims: 1. What demographic and tumor characteristics are predictive of survival in metastatic breast cancer? 2. What is the median duration of each sequential chemotherapy regimen and subsequent survival of women following each sequence of chemotherapy regimen in metastatic breast cancer? Methods: Retrospective study included 792 women diagnosed from January 1999 through December 2009 at the University of Pittsburgh Cancer Institute Breast Cancer Program. Results: Median duration of sequential chemotherapy regimen and median survival from completion of sequence of chemotherapy regimens were relatively short with a wide range of treatment duration and survival. Characteristics for poor survival included hormone status, human epidermal growth factor receptor-2 (HER 2/neu) status, and increased number and type of metastatic sites. Women who took more than the second sequential chemotherapy regimens had no more than median 3 months of treatment duration and 6 months survival from treatment termination. Discussion: Median clinical response and survival shorten with sequential chemotherapy regimen but with wide ranges. The rare clinical response of the minority should not set the standard for treatment expectations. All cancer clinicians, including oncology nurses, must ensure that patients are receiving tailored counseling regarding their specific risks and benefits for sequential metastatic breast cancer chemotherapy.